2020
DOI: 10.3390/cells9040933
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Mitochondria Quality Control Mechanisms and Cardiac Aging

Abstract: Cardiovascular disease (CVD) is the number one cause of death in the United States. Advancing age is a primary risk factor for developing CVD. Estimates indicate that 20% of the US population will be ≥65 years old by 2030. Direct expenditures for treating CVD in the older population combined with indirect costs, secondary to lost wages, are predicted to reach $1.1 trillion by 2035. Therefore, there is an eminent need to discover novel therapeutic targets and identify new interventions to delay, lessen the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 176 publications
1
23
0
Order By: Relevance
“…Additionally, the PI3K or Akt pharmacological inhibitor abrogated the protective effects of LS-102. It is essential for the dynamic balance of mitochondrial structure and function to maintain a functional heart as a response and adaptation to metabolic or environmental stresses (Yellon and Hausenloy, 2007;Walters et al, 2012;Kloner, 2017;Forte et al, 2020;Ghosh et al, 2020;Oh et al, 2020;Tong et al, 2020). We found that LS-102 significantly enhanced the survival rate of H9c2 cardiomyocytes by modulating mitochondria in the model of H/R-induced H9c2 cell injury.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, the PI3K or Akt pharmacological inhibitor abrogated the protective effects of LS-102. It is essential for the dynamic balance of mitochondrial structure and function to maintain a functional heart as a response and adaptation to metabolic or environmental stresses (Yellon and Hausenloy, 2007;Walters et al, 2012;Kloner, 2017;Forte et al, 2020;Ghosh et al, 2020;Oh et al, 2020;Tong et al, 2020). We found that LS-102 significantly enhanced the survival rate of H9c2 cardiomyocytes by modulating mitochondria in the model of H/R-induced H9c2 cell injury.…”
Section: Discussionmentioning
confidence: 77%
“…Lower expression of TSC2 in LEAD may be an effect of aging, a process with declined AMP-activated protein kinase (AMPK) signaling, which activates TSC2 [ 78 ]. One of the features of aging related to suppression of AMPK is lowering the autophagy, a process essential for degradation of protein aggregates forming in aging cells [ 79 ]. Lower level of autophagy could be also indicated by downregulation of promotor of aggrephagy TCPR1 in LEAD group [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 26S proteasome consists of a 20S proteolytic core particle that is flanked by two 19S lid particles. Upon recognition of the ubiquitinated substrate by the 19S lid, the substrate is translocated into the barrel shape of the proteasome and cleaved by proteases in the catalytic sites of the 20S core [ 105 , 108 ]. Proteasomal degradation of HIV-1 proteins may have both proviral and antiviral roles as reviewed in [ 109 ], including rhTRIM5a-mediated HIV-1 degradation.…”
Section: The Nexus Between Trim5α Antiviral Functions and Host Degmentioning
confidence: 99%